Predictors of compliance with payer-led oncology clinical pathways. Issue 28 (1st October 2022) - Mullangi, Samyukta; Chen, Xiaoxue; Pham, Timothy; Liu, Ying; Gordon, Aliza; Debono, David Joseph; Fisch, Michael Jordan; Gonen, Mithat; Hershman, Dawn L.
Abstract : 7 Background: Rising healthcare costs have garnered interest from payers in shifting oncology care towards a value-based practice model. Pathways are a subset of evidence-based guidelines designed to standardize cancer drug prescribing by clarifying decisions along three priorities: efficacy, safety, and cost. However, the major predictors of compliance with clinical pathway recommendations are unknown. Methods: We conducted a retrospective cohort study using administrative claims linked with prior authorization data of Anthem commercial and Medicare Advantage members. We identified members aged 18 or older with a diagnosis of breast, lung, colorectal, bladder, kidney, uterine, pancreatic cancer or melanoma being treated with a first-line treatment regimen in the metastatic setting between July 2018 and October 2021. The primary outcome was pathway compliance (PC), defined as whether a patient's anti-cancer drug regimen is also an Anthem pathway-endorsed regimen. We built a logistic regression model with stepwise backward selection to identify patient, physician, practice, geographic, and temporal factors that were associated with PC. Results: The cohort comprised 17, 584 patients in total. The treatment period yielded 11, 277 (64%) observations of patients with PC (48.1% male, mean [SD] age 60.7 years [11]) and 6, 307 (36%) without PC (45.1% male, mean [SD] age 60.4 years [11.6]). In adjusted analyses, we find that the odds of PC decrease over time and with variation by malignancy. Any inpatient (OR = 1.32, 95% CI 1.22 – 1.43) or emergency room utilization (OR = 1.21, 95% CI 1.12 – 1.31) in the baseline 6-month period was associated with a higher odds of PC. Conversely, doubling total medical costs in the preceding 6 months was associated with lower odds of PC (OR 0.86, 95% CI 0.83 – 0.88). The odds of PC increased with a higher share (median or above vs below median) of Anthem patients per physician (OR 1.12, 95% CI 1.04 – 1.20). Finally, Oncology Care Model participation was associated with higher odds of PC (OR = 1.13 95% CI 1.04 – 1.23). Conclusions: Among patients treated in the first-line setting for metastatic disease, PC was observed in slightly under two-thirds of cases and was associated with the penetration of Anthem patients in the practice. Participation in OCM was also associated with increased PC. These findings would be of interest to policymakers focused on value-based cancer care.